2023
DOI: 10.3390/su15031834
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Harbor Dredged Sediment for Sustainable Reuse as Construction Material

Abstract: An unprecedented rate of construction has profoundly increased the risk of scarcity of natural resources and threatened ecosystem sustainability. To establish an effective sustainable development policy, it is imperative to promote the use of responsible production channels, including waste recycling. Reuse of harbor dredged sediment is commonly investigated as a valuable alternative to non-renewable natural resources needed for construction. Sediment characterization is decisive in the valorization process, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…An examination of these works revealed that 3 papers (10%) utilized experimental methodology, 6 papers (21%) discussed the reported results and compared them with their findings, and 20 papers (69%) cited 1 or more of Dr. Santos’s papers in the introduction section of their papers to explain a concept (Table S1 in the Supporting Information). More details and discussion about these relevant studies ,, are available in the Supporting Information file alongside other analyses on citation usage, publication sources, country, institutional collaboration analyses, and paper classification according to scientific disciplines and the United Nations Sustainable Development Goals. A scientometric analysis is a powerful tool for researchers to gauge the impact of their work and to connect with the broader scientific community beyond what other networking activities, such as conferences and webinars, allow.…”
Section: Scientometric Analysismentioning
confidence: 99%
“…An examination of these works revealed that 3 papers (10%) utilized experimental methodology, 6 papers (21%) discussed the reported results and compared them with their findings, and 20 papers (69%) cited 1 or more of Dr. Santos’s papers in the introduction section of their papers to explain a concept (Table S1 in the Supporting Information). More details and discussion about these relevant studies ,, are available in the Supporting Information file alongside other analyses on citation usage, publication sources, country, institutional collaboration analyses, and paper classification according to scientific disciplines and the United Nations Sustainable Development Goals. A scientometric analysis is a powerful tool for researchers to gauge the impact of their work and to connect with the broader scientific community beyond what other networking activities, such as conferences and webinars, allow.…”
Section: Scientometric Analysismentioning
confidence: 99%
“…Sediment is dredged to maintain the navigability of waterways, control floods, or remove contaminated sediment. Several potential usages of dredged sediment include its use in preventing coastal erosion, reconstructing landscapes [ 15 ], and usage as a construction and building material [ 16 ]. Additionally, there is potential for using dredged sediment in agriculture due to its high content of organic matter and other nutrients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This process involves the disposal of sediment, sand, and other debris that has been removed from the sea floor during dredging operations. The importance of dumping dredged material in the ocean is linked to several key factors, including the need for safe and efficient navigation, the protection of the marine environment, and the management of waste from dredging operations (Bortali et al, 2023). In recent years, mounting concern has arisen over the environmental consequences of seabed dredging and subsequent dumping of dredged material into the ocean.…”
Section: Introductionmentioning
confidence: 99%